Should Everybody Learn to Code? - Shein, Esther (Communications of the ACM, 2014)
The article focuses on computer science and coding education. It states that demand in the U.S. for computer scientists and technical professionals is forecast to grow by 34 percent through 2018 and mentions a study that found many people were programming without realizing it by creating database queries using SQL or creating macros for spreadsheets. It comments on the need for people to learn computational thinking to think abstractly and learning problem-solving skills in computer science. It talks about the state of computer science in public education, reporting that only 12 percent of U.S. high schools offer computer science courses, and speculates on the benefits of teaching computer science concepts starting at age five or six.